Community and public health nursing - Nies, Mary A.; McEwen, Melanie (St. Louis, Missouri : Elsevier Science, 2020)
This comprehensive text has been renamed as Community Public Health Nursing to reflect the addition of six new chapters in this edition on Global Health and emerging fields of public health nursing.
Unit 1 Introduction to Community Health Nursing -- Unit 2 The Art and Science of Community Health Nursing -- Unit 3 Caring for the Community toward Health and Development -- Unit 4 Care of population groups and public health services -- Unit 5 Data Management in pubic health.
Includes bibliographical references and index.
Keywords: COMMUNITY HEALTH NURSING